2014
DOI: 10.1063/1.4851337
|View full text |Cite
|
Sign up to set email alerts
|

Composite and shaped pulses for efficient and robust pumping of disconnected eigenstates in magnetic resonance

Abstract: ‡ These authors contributed equally.Long-lived (symmetry protected) hyperpolarized spin states offer important new opportunities (for example, in clinical MR imaging), but existing methods for producing these states are limited by either excess energy dissipation or high sensitivity to inhomogeneities. We extend recent work on continuouswave irradiation of nearly-equivalent spins (spin-lock induced crossing) by designing composite pulse and adiabatic shaped-pulse excitations which overcome the limitations. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 41 publications
1
95
0
Order By: Relevance
“…The small chemical shift difference allows access to the long-lived singlet order of the CH 2 D protons, by using radiofrequency pulse techniques which operate in the nearequivalence regime [33][34][35][36]. In the current study, we used the SLIC (Spin-Lock Induced Crossing) method [35], as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The small chemical shift difference allows access to the long-lived singlet order of the CH 2 D protons, by using radiofrequency pulse techniques which operate in the nearequivalence regime [33][34][35][36]. In the current study, we used the SLIC (Spin-Lock Induced Crossing) method [35], as shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…In those cases, however, the coupling between singlet and triplet state is weak and therefore an ad-hoc methodology is needed to manipulate singlet order. The two methods proposed, magnetisation-to-singlet conversion (M2S) [37,38] and spin-lock induced crossing (SLIC) [40,41], are discussed below.…”
Section: Singlet Order and Magnetic Equivalencementioning
confidence: 99%
“…Three techniques have been proposed for manipulating singlet order in this regime: (i) magnetisation-to-singlet conversion (M2S) [37,38] (ii) its reverse, singlet-to-magnetisation (S2M); and (iii) spinlock induced crossing (SLC) [40,41], which works in both directions. The M2S and S2M pulse sequences can transform longitudinal into singlet order (and vice versa), as shown in Fig.…”
Section: M2s Pulse Sequencesmentioning
confidence: 99%
See 2 more Smart Citations